The spending and debt response to minimum wage hikes - Daniel Aaronson; Sumit Agarwal; Eric French (Federal Reserve Bank of Chicago, 2008)
Following a minimum wage hike, spending increases more than income, and thus debt rises, in households with minimum wage workers. The size, as well as the timing, persistence, composition, and distribution of the spending response is inconsistent with the basic certainty equivalent life cycle model. However, the response is consistent with a model where households can borrow against part of the value of their durable goods.
Keywords: 330